Post-abortion long-acting reversible contraception in a sample of Italian women: intrauterine device versus subdermal implant. (4th May 2019) - Piva, I.; Brusca, F.; Tassinati, F.; Bonipozzi, S.; Palano, A.; Sassi, M. T.; Bonaccorsi, G.; Morano, D.; Martinello, R.; Scutiero, G.; Indraccolo, U.; Greco, P.
Abstract: Long-acting reversible contraceptives (LARC) represent an especially effective kind of post-abortion contraception. We aimed at assessing satisfaction, discontinuation, efficacy, and tolerability associated with either levonorgestrel intrauterine device (L-IUCD), the copper intrauterine device (C-IUCD) and implant (IMP) after termination of pregnancy (TOP). We recorded baseline data about the patients and performed phone surveys at 3, 6 and 12 months after insertion to assess the bleeding profile. Furthermore, women were inquired about possible adverse events, satisfaction, and discontinuation at 12 months after insertion. LARC continuers (>12 months after TOP) were divided into three groups: L-IUCD ( n = 47), C-IUCD ( n = 6) and IMP ( n = 36). Satisfaction rates among L-IUCD users were higher than among IMP users (100% vs. 72.2%, p < .05). A higher, yet not significant, share of patients decided to withdraw contraception in IMP group (3.6% in IUCD group and 12.2% in IMP group). The bleeding profile was significantly more favorable among L-IUCD users than among IMP users. Finally, the reported rate of treatment-associated adverse events did not differ significantly among the groups. L-IUCD insertion after TOP is associated with higher satisfaction and lower discontinuation rates than IMP. Such pattern could be attributed to a more favorable bleeding profile.